Evaluation of GPS observations accuracy within limited visibility basing on empiric data - Yanchuk, Oleksandr; Roman, Shulgan; Dets, Tetiana; Struk, Stanislav (Geodesy and Cartography, 2017)
In this paper, the exploration of accuracy of empirical GPS observations within the limited horizon has been conducted. The exploration has been done by assessing the outcome accuracy conducted at six points with a different percentage of limited horizon. The accuracy evaluation has been done in two variants. In the first one, the measured values of one-hour sessions have been compared with the values for the whole period of observations (6–12 hours) taken as standard. In the second variant, in order to get the independent data check, the measurement of distances and heights differences between the indicated points using the electronic total station has been conducted. In the second variant, the accuracy evaluation has been done basing on outcome deviations of one-hour session observations from the values measured by electronic total station. As the inadequate results of accuracy have been received (on the level of dozens of centimeters), it has been decided to check the measurements accuracy on observation sessions with a minimal value of DOP. In order to do this the preliminary planning has been completed and the optimal onehour sessions of observations at each point have been selected. After that, the absolute errors of observation outcomes have been calculated at these points in both mentioned above variants. The research results prove that upon doing the preliminary planning the accuracy on the level of 0.5–3 cm can be achieved.